Rol de enfermería y su relación en la atención a pacientes embarazadas con alto riesgo que acuden al área de emergencia obstétrica del Hospital Martin Icaza. octubre 2018 – abril 2019 - Flores Vargas, Elva Marlene (2019)
Having as problematic the different dissatisfactions and disadvantages exhibited by the users regarding the quality of care received in the health institutions of the Babahoyo canton, this study focuses on determining the role of nursing and its relationship in the care of pregnant patients with high risk who come to the Obstetric Emergency Area of the Martin Icaza Hospital. October 2018 - April 2019. . In the development of this research work, the scientific, hypothetical, deductive, and descriptive method is applied; and the qualitative-quantitative modality. Framing the types of research: bibliographic or documentary, descriptive and transversal. The technique of data collection to be used is the interview and the survey, applying questionnaires of questions to users and nursing professionals of the Obstetric Emergency area of the Martin Icaza Hospital. After the analysis of the information of the interview and survey, it was established that the nursing care and research role directly influences the quality and warmth of the attention perceived by the users in this health house, since the results show that only 11.1% have a specialization in obstetric emergencies, and 33.3% show a lack of knowledge in pharmacology, greatly harming the actions to be taken by this group of pregnant women at high risk. In the user surveys it was possible to identify that 72.7% of them stated that the nursing professionals are not very poorly qualified to care for this group of pregnant women at high risk; and 63.6% are not very satisfied with the care received, stating that the professionals do not have the scientific knowledge to meet the needs of this group of pregnant women. Concluding that the role of care and research is of great importance to avoid further complications, and thus reduce the rates of maternal and fetal morbidity and mortality.